Convalescence plasma treatment of COVID-19: results from a prematurely terminated randomized controlled open-label study in Southern Sweden - Karin Holm (BMC, 2021)
Abstract Objective Convalescent plasma has been tried as therapy for various viral infections. Early observational studies of convalescent plasma treatment for hospitalized COVID-19 patients were promising, but randomized controlled studies were lacking at the time. The objective of this study was to investigate if convalescent plasma is beneficial to hospitalized patients with COVID-19. Results Hospitalized patients with confirmed COVID-19 and an oxygen saturation below 94% were randomized 1:1 to receive convalescent plasma in addition to standard of care or standard of care only. The primary outcome was number of days of oxygen treatment to keep saturation above 93% within 28 days from inclusion. The study was prematurely terminated when thirty-one of 100 intended patients had been included. The median time of oxygen treatment among survivors was 11 days (IQR 6–15) for the convalescent plasma group and 7 days (IQR 5–9) for the standard of care group (p = 0.4, median difference -4). Two patients in the convalescent plasma group and three patients in the standard of care group died (p = 0.64, OR 0.49, 95% CI 0.08–2.79). Thus no significant differences were observed between the groups. Trial registration ClinicalTrials NCT04600440, retrospectively registered Oct 23, 2020.